A decision support system for resource intervention in real-time emergency management. (12th February 2007) - Minciardi, Riccardo; Sacile, Roberto; Trasforini, Eva
In the emergency management related to either natural or anthropogenic disasters, transport and communication infrastructures play a key role for a good realisation of the emergency plans. Communication in this phase is essential both from a bottom-up (information related to the actual state of a catastrophic event), and from a top-down point of view (information related to the policy of the decision makers relevant to resources management). On the other hand, the importance of transport infrastructures is fundamental, as it is an essential instrument for emergency resource intervention, as well as for population evacuation. Thus, an effort should be made in order to define instruments capable of aiding decision makers in using infrastructures during emergency management. In this paper, a Decision Support System (DSS) for resource intervention in real-time emergency management is proposed. The general methodological framework and the mathematical formulation of one of the problems solved by the DSS are described.